CONCERNING THE MATHEMATICAL QUALITY KNOWLEDGE OF MODERN UNIVERSITY ENTRANTS - E. A. Rapotsevich; E. N. Kolyman (Образование и наука)
The aim of the article is to analyze the dynamics of Unified State Examination GPA on Mathematics in Novosibirsk Region, Russia over the last two years.Methods. For diagnosing the Mathematics quality digestion of general education institution graduates, the authors apply the empirical material; correlation relationship between entrance test results and the results of Unified State Examination is assessed.Results. The research findings include the main causes of low results in Mathematics; one of them is the absence of clear conceptual thinking. The authors give the analysis of residual assessment for school mathematical knowledge during the entrance test results of incoming first-year students (brunches ofstudy: Public and Municipal Administration, Human Resource Management) of Siberian Management Institute, Siberian Affiliate of Russian Presidential Academy of National Economy and Public Administration (Siberian Affiliate of RANEPA). The conclusion is drawn that the result of Unified State Examination isn’t an objectiveindicator of mathematical knowledge of the incoming first-year students.Scientific novelty. The authors single out the key factors caused low mathematical knowledge quality of school graduates. Correction ways and concrete steps to be taken for improving students’ assimilation of Bachelor’s Programme Science Disciplines are described. Practical significance. The authors note that the research outcomes can be used not only for improving Unified State Examination probity and objectivity of students’ quality assessment but for increasing basic Mathematics education as well